DEVELOPMENT OF INTERACTIVE EDUCATIONAL MEDIA FOR PREVENTING ANEMIA IN TEENAGE GIRL BASED ON E-FLIPBOOKS AS AN EFFORT TO ACCELERATE STUNTING REDUCTION - Ferdina, Cucun Setya; Vardila Putri, Nindi Pramesthi; -, Lailaturohmah (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Stunting or short toddlers is currently one of the toddlers problems toddlers in the world. Stunting is important because it concerns about the quality of Indonesia's human resources in the future. The incidence of stunting is a cycle. Children born to mothers who are anemic will suffer stunting in the future and continue without stopping, which is called the intergenerational stunting cycle. Improving adolescent nutrition before conception is one way to break the intergenerational cycle of stunting. This research aims to develop interactive educational media for preventing anemia in adolescents based on e-flipbooks as an effort to accelerate stunting reduction. The research method used is Research and Development (R&D), with the final results of this research is producing an e-flipbook for preventing anemia in adolescents. The research instrument used a questionnaire. There are 2 data analyzes used, qualitative and quantitative analysis. The validation test results from material experts and media experts stated that this educational media for preventing anemia in adolescents is very suitable for use with a percentage of 90%. And the results of field trials on anemia prevention educational media are mostly in the very feasible category with a percentage of 87.03%.